Effects of a multi-professional intervention on body composition, physical fitness and biochemical markers in overweight COVID-19 survivors: a clinical trial - Sordi, Ana Flávia; Lemos, Maurício Medeiros; de Souza Marques, Déborah Cristina; Ryal, Joed Jacinto; Priscila de Paula Silva Lalucci, Marielle; Marques, Marilene Guiraldi; Amaro Camilo, Maria Luiza; De Paula Ramos, Solange; Franzói De Moraes, Solange Marta; Valdés-Badilla, Pablo; Mota, Jorge; Magnani Branco, Braulio Henrique (Frontiers in Physiology, 2023)
Introduction: The sequelae post-COVID can affect different systems. In this sense, considering the multi-factorial etiology of COVID-19, multi-professional interventions could be a relevant strategy for recovery health indicators. Objective: This study aimed to investigate the effects of multi-professional intervention on body composition, physical fitness, and biomarkers in overweight COVID-19 survivors with different symptomatology. Methodology: A non-randomized parallel group intervention included 69 volunteers (BMI ≥25 kg/m2), divided into three groups according to SARS CoV-2 symptomatology, but only 35 finished the longitudinal protocol [control group (n = 11); moderate group (n = 17) and severe group (n = 7)]. The groups were submitted to a multi-professional program (nutritional intervention, psychoeducation, and physical exercise intervention) for 8 weeks, and the volunteers underwent body composition assessments (primary outcome) and physical and biochemical tests (secondary outcome) in pre- and post-intervention. This study was registered on the Clinical Trials Registration Platform number: RBR-4mxg57b and with the local research ethics committee protocol under number: 4,546,726/2021. Results: After the 8-week multi-professional intervention, the following results were observed for the moderate COVID-19 group: improved dynamic strength of lower- and (p = 0.003), upper-limbs (p = 0.008), maximal isometric lumbar-traction strength (p = 0.04), flexibility (p = 0.0006), and albumin (p = 0.0005), as well as a reduction in the C reactive protein (CRP) (p = 0.003) and fasting glucose (p = 0.001); for the severe COVID-19 group: an improvement in dynamic lower-body strength (p = 0.001), higher values of albumin (p = 0.005) and HDL-c (p = 0.002), and lower values of CRP (p = 0.05), and for the control group: an improvement in sit-up repetitions (p = 0.008), and a reduction of CRP (p = 0.01), fasting glucose (p = 0.001) and total cholesterol (p = 0.04) were identified. All experimental groups reduced triglycerides after intervention (p < 0.05). Conclusion: Finally, 8 weeks of multiprofessional intervention can be an efficient tool for reversing the inflammatory process and promoting improvements in daily activities and quality of life, although it is believed that the severe COVID-19 group needs longer interventions to improve different health indicators. Clinical Trial Registration:https://ensaiosclinicos.gov.br/, identifier: RBR-4mxg57b.